Experiencing the Improbable: Rare Events and Organizational Learning - Lampel, Joseph; Shamsie, Jamal; Shapira, Zur (Organization Science, 2009)
Organizations that go through rare and unusual events, whether they are costly or beneficial, face the challenge of interpreting and learning from these experiences. Although research suggests that organizations respond to this challenge in a variety of ways, we lack a framework for comparing and analyzing how organizational learning is affected by rare events. This paper develops such a framework. We begin by first outlining two views of rare events. The first view defines rare events as probability estimates, usually calculated from the frequency of the event. The second view defines rare events as opportunities for unique sensemaking based on the enacted salience of specific features of the rare events. We next use these definitions to explore how rare events trigger learning, and then examine the kind of learning processes that are triggered by rare events. We conclude with a discussion of promising areas of research on learning from rare events.